Gynecological Surgery and COVID-19: What is the Impact and How Should I Manage it? - Julio Cesar Rosa-; Paulo Ayroza Ribeiro; Luiz Gustavo Oliveira Brito; Mariano Tamura Vieira Gomes; Sergio Podgaec; Helizabet Salomão Abdalla Ayroza Ribeiro; Carlos Augusto Pires Costa Lino; Ricardo Quintairos; Walquiria Quida Salles Pereira Primo; Agnaldo Lopes da Silva Filho (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract It is estimated that around 28 million surgeries will be postponed or canceled worldwide as a result of this pandemic, causing a delay in the diagnosis and treatment of more than 2 million cancer cases. In Brazil, both the National Health Agency (ANS) and National Health Surveillance Agency (ANVISA) advised the postponement of elective and non-essential surgeries, causing a considerable impact on the number of surgical procedures that decreased by 33.4% in this period. However, some women need treatment for various gynecological diseases that cannot be postponed. The purpose of this article is to present recommendations on surgical treatment during the COVID-19 pandemic.